MRI-based assessment paraspinal extensor muscle fatty infiltration in acute cervical spinal cord injury patients - a retrospective study - Liao, Yang; Lin, Xuping; Su, Wanhan; Wu, Xiuming; Wang, Xiaomen; Yang, Wencheng; Lu, Haichuan; Huang, Chunhui; Wu, Yiqi (BMC musculoskeletal disorders, 2024)
The effect of fat infiltration in the paraspinal muscles on cervical degenerative disease has been confirmed by multiple studies. However, little is known about fat infiltration in the paraspinal extensors in patients with acute cervical spinal cord injury (SCI). This study aimed to investigate the difference in paraspinal extensor fatty infiltration between patients with acute cervical SCI and healthy controls, and to further explore the protective role of the paravertebral extensor muscles in patients with cervical SCI. A total of 50 patients with acute cervical SCI admitted to the emergency department from January 2019 to November 2023 were retrospectively analyzed, including 26 males and 24 females, with an average age of 59.60 ± 10.81 years. A control group of 50 healthy middle-aged and elderly individuals was also included, comprising 28 males and 22 females, with an average age of 55.00 ± 8.21 years. Cervical spine magnetic resonance imaging (MRI) was used to measure the cross-sectional areas of the superficial and deep cervical extensor muscles, the corresponding vertebral body cross-sectional areas, and the fat area within the superficial and deep extensor muscle groups using Image J software. Differences between the two groups were compared, and the cervical SCI patients were further analyzed based on the severity of the spinal cord injury and gender differences. The deep fatty infiltration ratio (DFIR) and superficial fatty infiltration ratio (SFIR) at C4-C7 in the cervical SCI group were significantly higher than those in the control group (P < 0.001). The cross-sectional area of the functional deep extensor area (FDEA) relative to the vertebral body area (VBA) and the cross-sectional area of the functional superficial extensor area (FSEA) relative to the VBA at the C5 and C6 levels in the cervical SCI group were significantly lower than those in the control group (P < 0.001, P < 0.001, P = 0.034, P = 0.004 respectively). Among the cervical SCI patients, the cross-sectional areas of the deep extensor area (DEA) and the superficial extensor area (SEA) in males were significantly higher than those in females (P < 0.001). At the C6 and C7 levels, the FDEA/VBA and FSEA/VBA ratios in the male group were higher than those in the female group (P = 0.009, P = 0.022, P = 0.019, P = 0.005, respectively). Patients with acute cervical SCI exhibit significantly higher fatty infiltration and a greater degree of paravertebral extensor muscle degeneration compared to healthy controls. This finding underscores the importance of the paravertebral extensor muscles in the context of cervical SCI and may guide future therapeutic strategies.